Implementation of a Departmental Female Emergency Medicine Physician Group - Parekh, Kendra P. (West J Emerg Med, 2019)
Gender disparities exist in academic emergency medicine (EM). We developed and implemented a female EM physician group – Women in Academic Emergency Medicine (WAM) – to support female EM residents, fellows, and faculty. The goal of WAM is to provide a support system through mentorship, education, and outreach. A targeted needs assessment was completed to identify goals and objectives specific to our department. In the first full year of implementation, WAM hosted eight events, including three topical dinners and one formal panel. Of 42 female faculty and residents, 40 (95%) attended at least one WAM event, and all (20/20) of the female faculty strongly supported WAM. WAM advocated for increased female physician representation on the department’s Physician Executive Leadership Group and preservation of dedicated lactation space in the emergency department. Using a needs assessment, the process of developing WAM can be replicated in any department to create a female physician group.